Growing up Filipino 3 new stories for young adults - Brainard, Cecilia Manguerra 1947-; Brainard, Cecilia Manguerra 1947- (University of Santo Tomas Publishing House, 2022)
Collects 25 short stories by Filipino authors in the US and the Philippines about what it means to be young and Filipino. The stories explore the universal themes of coming-of-age, love, angst, family, relationships, and other young adult issues. The stories reveal Filipino and Filipino American culture, mores, history, society, politics, and other nuances. For instance, Filipino respect for their elders, extended families, religious practices, funereal rites, love for folklore are apparent in the stories. GROWING UP FILIPINO 3: NEW STORIES FOR YOUNG ADULTS follows two earlier critically acclaimed books. --Provided by publisher.